KONTRIBUSI PERBANKAN SYARIAH TERHADAP STABILITAS EKONOMI DAN PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) MELALUI PEMBIAYAAN SYARIAH - Richen Shofia Nisa'; Ima Kurniawati; Muhammad Ritjha; Vionika Yolla Pramadita; Amalia Nuril Hidayati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the contribution of Islamic banking to national economic stability and examine the role of Sharia-based financing in accelerating the achievement of the SDGs in Indonesia. The method employed is a qualitative-descriptive approach through library research. Data were obtained from official publications of national financial institutions, reports from regulators such as the Financial Services Authority (OJK) and Bank Indonesia (BI), as well as relevant academic articles and literature on Islamic banking, economic stability, and the SDGs. The results show that Islamic banking contributes to economic stability through three main mechanisms: (1) reducing speculative risks through asset-based and profit-sharing financing; (2) enhancing financial inclusion by supporting MSMEs and public housing; and (3) strengthening long-term financing through Islamic capital market instruments such as green sukuk. Furthermore, Sharia-based financing supports the achievement of several SDG targets, including poverty alleviation (SDG 1), decent work and economic growth (SDG 8), sustainable cities and communities (SDG 11), and climate action (SDG 13).